Diagnosis and treatment of splenic artery steal syndrome after liver transplantation. Issue 4 (9th January 2022) - Avanaz, Ali; Avanaz, Ezgi; Kisaoglu, Abdullah; Yilmaz, Vural Taner; Demiryilmaz, Ismail; Aydinli, Bulent
Abstract: Introduction: Splenic artery steal syndrome is a phenomenon which cause graft ischaemia and dysfunction after liver transplantation. Case Presentation: A 31 year old women underwent living donor liver transplantation (LDLT) with a diagnosis of cryptogenic liver cirrhosis. In postoperative follow‐up liver enzymes were elevated. Dynamic computed tomography and digital subtraction angiography revealed splenic artery steal syndrome. Splenic artery ligation was performed for treatment. Discussion: The diagnosis of splenic artery steal syndrome is made by the presence of slowed hepatic artery flow compared to the splenic artery without hepatic artery thrombosis or stenosis on digital subtraction angiography. Conclusion: Although interventional radiological procedures are the first‐line treatment method, surgical treatment methods (splenectomy, splenic artery ligation) are successful in increasing hepatic artery flow.